Effects of passive repeated plyometric training on specific kicking performance of elite Olympic taekwondo player - Wang, H.-H.; Liu, C.; Chu, M.-Y.; Ho, W.-H.; Shiang, T. Y. (ISB Congress, 2005)
Many researches indicated that passive repeated plyometric training (PRP) could improve neuromuscular system of general players. However, it is not clear how much training effect can beneficial to elite players. Hence, the aim of this study was to determine the effects on specific kicking performance of a 6-wk PRP training program of elite Olympic Taekwondo player. The results indicate that a PRP training program could improve the velocity and power of kicking of elite Taekwondo player in a sport specific kicking performance. Based on the results of this study, authors believe that PRP training is an efficient method of training for elite players to improve strength and power. Therefore, PRP training could be used for those sports activities that involve high muscle speed